Diversity of phytoplankton associated with water quality in selected Area in Bintulu, Sarawak - Petruson Asan Bajing
Bintulu is one of the largest industrial area where it located in the middle parts of Sarawak with a total area of 7,220.40 square kilometers including 2 others district which is Sebauh and Tatau. Unfortunately, there are lack of information regarding the phytoplankton species especially on freshwater environments has been measured in the current study area. The early hypothesis stated that the high diversity of phytoplankton can be used as an indicator for water quality conditions. In-situ and ex-situ method which include 12 water quality parameters has been measured, which is consisting of temperature, dissolve oxygen, salinity, turbidity, pH, total dissolved solids, conductivity, total suspended solids, nitrite, nitrate, ammonia, and phosphate. Physico-chemical of water not showing a significant result. While, correlation coefficient shows both positive and negative result on several phytoplankton species and physico-chemical of water. Physico-chemical of water is affecting the phytoplankton availability in each sampling station, as for the phytoplankton species recorded in each sampling station is different.